Molecular docking of noni fruit extract (M. citrifolia L.) active compound as a radiation protection agent: a bioinformatic approach - Saputra, Deny; Mulyani, Sri Wigati Mardi; Ramadhani, Nastiti Faradilla; Margareth, Jane Evelyn; Putri, Regita Maharani Kharisma; Harlens, Farah Tariza; Nugraha, Alexander Patera (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Noni fruit (M. citrifolia L.) is a medicinal plant known for its antioxidant bioactive compounds, which have potential use as radiation protection agents. Despite their traditional use, the specific bioactive compounds and their efficacy as radiation protectants have not been thoroughly investigated. This study aims to address this research gap by evaluating the potential of noni fruit extract as a candidate for radiation protection using in-silico methods. Databases consulted include PubChem, PASS Online, and ProTox-II. The results identified nine bioactive compounds in noni fruit extract: quercetin, kaempferol, morindin, morindone, alizarin, nicotinamide, beta-sitosterol, squalene, and n-hexadecanoic acid. Among these, kaempferol, squalene, and n-hexadecanoic acid were found to be the most potent antioxidants. Kaempferol exhibited a low toxicity level (grade 5) with significant activity as an antioxidant (Pa ≥ 0.7), free radical scavenger (Pa ≥ 0.7), and radioprotector (Pa 0.3 – 0.7). Squalene, a triterpene with low toxicity (class 5), showed antioxidant activity (Pa 0.3 – 0.7), free radical scavenger activity (Pa 0.3 – 0.7), and radioprotection (Pa 0.3 – 0.7). n-Hexadecanoic acid, a metabolite with moderate toxicity (class 4), demonstrated lower antioxidant activity (Pa ≤ 0.3), while morindin exhibited free radical scavenging and radioprotective properties. The findings suggest that kaempferol, squalene, and n-hexadecanoic acid in noni fruit extract hold promise as candidates for radiation protection, as evidenced by in-silico analysis.